2020
DOI: 10.3390/ijms22010053
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates Reduce Smoking-Induced Osteoporotic-Like Alterations by Regulating RANKL/OPG in an Osteoblast and Osteoclast Co-Culture Model

Abstract: Co-culture models have become mandatory for obtaining better insights into bone homeostasis, which relies on the balance between osteoblasts and osteoclasts. Cigarette smoking (CS) has been proven to increase the risk of osteoporosis; however, there is currently no proven treatment for osteoporosis in smokers excluding cessation. Bisphosphonates (BPs) are classical anti-osteoclastic drugs that are commonly used in examining the suitability of bone co-culture systems in vitro as well as to verify the response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…TRAP 5b activity as a marker of osteoclast activity was measured in culture supernatants as previously described [30,31]. Culture supernatant (30 µL) was transferred to a new cell culture plate with 90 μL of TRAP 5b activity assay solution (0.2% w/v 4-nitrophenyl phosphate, 100 mM sodium…”
Section: Tartrate-resistant Acid Phosphatase (Trap) 5b Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…TRAP 5b activity as a marker of osteoclast activity was measured in culture supernatants as previously described [30,31]. Culture supernatant (30 µL) was transferred to a new cell culture plate with 90 μL of TRAP 5b activity assay solution (0.2% w/v 4-nitrophenyl phosphate, 100 mM sodium…”
Section: Tartrate-resistant Acid Phosphatase (Trap) 5b Activitymentioning
confidence: 99%
“…Bright-field images of the stained cells were captured by microscopy (EVOS FL, Thermo Fisher Scientific). For quantitative measurement, the bound Alizarin Red was dissolved with 10% w/v cetylpyridinium chloride solution and quantified photometrically (λ = 562 nm; Omega plate reader) as described previously [31].…”
Section: Alizarin Red Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, nutritional support, especially an adequate intake of vitamin D and calcium, constitutes an essential element of the therapy [20]. In turn, bisphosphonates are common anti-osteoclastic drugs, but they also reduce cigarette smoking-induced osteoporotic alterations of osteoblasts and osteoclasts [21].…”
Section: Introductionmentioning
confidence: 99%
“…According to Zhu et al, bisphosphonates may be drugs for osteoporotic patients, especially smokers [21]. Many studies showed that bisphosphonates increase OPG expression and inhibit the expression of RANKL, which is opposed to the impact of nicotine on OPG/RANKL/RANK pathway [31,32].…”
Section: Introductionmentioning
confidence: 99%